Pentingnya Pola Asuh Anak Dalam Pebaikan Gizi Untuk Mencegah Stunting Sejak Dini di Desa Brumbungan Lor Kecamatan Gending Kabupaten Probolinggo - Dedi Joko Hermawan; Hermanto Hermanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2020)
Stunting is a chronic malnutrition problem caused by a lack of nutritional intake for a long time, resulting in growth problems in children, namely the child's height is lower or shorter (stunted) than the standard age. In addition to nutritional factors, stunting is caused by a lack of public knowledge, especially mothers who have babies and toddlers about stunting. The implementation method in the community service program is through providing counseling on stunting to mothers who have babies and toddlers in Brumbungan Lor Village, Gending District, Probolinggo Regency. The population in this study were mothers in Brumbungan Lor village who had babies and toddlers. The purpose of this counseling is to provide information about